2009
DOI: 10.4049/jimmunol.0902813
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironments Direct the Recruitment and Expansion of Human Th17 Cells

Abstract: Although Th17 cells play critical roles in the pathogenesis of many inflammatory and autoimmune diseases, their prevalence among tumor-infiltrating lymphocytes (TILs) and function in human tumor immunity remains largely unknown. We have recently demonstrated high percentages of Th17 cells in TILs from ovarian cancer patients, but the mechanisms of accumulation of these Th17 cells in the tumor microenvironment are still unclear. In this study, we further showed elevated Th17 cell populations in the TILs obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
237
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(257 citation statements)
references
References 56 publications
17
237
1
2
Order By: Relevance
“…In the present study, the expression of IL-17 protein was decreased in the biopsies of benign lesions (FTA and goiter tissues) when compared to malignant lesions (DTC and MTC). We hypothesize that the increased cytokine expression in the tumor environment may be associated with tumor progression, which is in agreement with the findings of Su et al (34) who demonstrated that a high number of CD4+ Th17 cells were present in melanoma, ovarian, breast and colon carcinomas (34). In the present study, the lymphocytes present in the tumor microenvironment of the MTC group tumors expressed the highest level of IL-17 expression compared with the DTC, FTA and goiter groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, the expression of IL-17 protein was decreased in the biopsies of benign lesions (FTA and goiter tissues) when compared to malignant lesions (DTC and MTC). We hypothesize that the increased cytokine expression in the tumor environment may be associated with tumor progression, which is in agreement with the findings of Su et al (34) who demonstrated that a high number of CD4+ Th17 cells were present in melanoma, ovarian, breast and colon carcinomas (34). In the present study, the lymphocytes present in the tumor microenvironment of the MTC group tumors expressed the highest level of IL-17 expression compared with the DTC, FTA and goiter groups.…”
Section: Discussionsupporting
confidence: 82%
“…The exact mechanism underlying this interaction remains unclear; however; we hypothesize that these molecules are important in the progression of cancer. Th17 cells have been identified in a number of human tumor types, including lymphoma (40), myeloma (41), breast (34) and ovarian cancer (42). In colorectal carcinomas, prognosis is influenced by Th17 expression; patients with high Th17 expression exhibit a poor prognosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, this population still represented less than 1% of the total CD4+ T cell population. The relative frequency of T H 17 cells in blood was not altered and a comparable recruitment of these cells to solid tumours has also been reported [23]. T H 17 cells may play a particularly important role in the development of clinical complications of paraproteinaemia and have been linked to problems such as bone disease.…”
Section: Oncotarget 30389 Wwwimpactjournalscom/oncotargetmentioning
confidence: 80%
“…The role of regulatory T cells in the development of MM is also under debate and remains controversial [8][9][10][11][12]. T H 17 cells are also of considerable interest in relation to tumour immunity and are increased in both the marrow and blood of patient with paraproteinaemia [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Research Papermentioning
confidence: 99%
“…The cytokines produced by the Treg profile has been described as potent inhibitors of antitumor immune response and are associated with poor prognosis for many types of cancer (Hiraoka et al, 2006;Downey et al, 2007;Fecci et al, 2007;Fu et al, 2007). The discovery of Th17 cells and their role in protecting the host against infectious agents and pathogenesis of several inflammatory and autoimmune diseases resulted in the raise of immunological research and its role in human cancer is still under investigation (Park et al, 2005;Yang and Ansell, 2009;Su et al, 2010).…”
Section: Adaptative Immune and Cancermentioning
confidence: 99%